2008
DOI: 10.1002/bjs.6137
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of younger patients with acute diverticulitis

Abstract: First episodes of acute diverticulitis were not more aggressive in patients aged 50 years or less. Recurrence rates were slightly higher than in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
12

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 37 publications
1
38
1
12
Order By: Relevance
“…During the follow-up of that study (5.2 years), only one of the 259 younger patients (0.5%) presented at a later date with perforation. More recently, Hjern et al 16 followed 234 patients and found that surgical management during the first admission was undertaken less commonly in younger than in older patients (2% vs 6.8%). During follow-up (30 months), no statistical difference between the 2 groups was observed in recurrent diverticulitis or need for further surgery.…”
Section: Discussionmentioning
confidence: 99%
“…During the follow-up of that study (5.2 years), only one of the 259 younger patients (0.5%) presented at a later date with perforation. More recently, Hjern et al 16 followed 234 patients and found that surgical management during the first admission was undertaken less commonly in younger than in older patients (2% vs 6.8%). During follow-up (30 months), no statistical difference between the 2 groups was observed in recurrent diverticulitis or need for further surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they also noted that complicated recurrence rate was significantly greater in patients who presented with complicated initial disease in comparison with those who did not present with a complicated disease. On the contrary, two retrospective studies did not reach the same conclusions, finding no influence related to CT severity on the outcome after a first episode of diverticulitis treated medically [18,19]. …”
Section: Discussionmentioning
confidence: 88%
“…9 Of 221 patients treated medically following a first admission with acute diverticulitis, overall readmission was 20.8% (46/221). 10 A further study of 502 patients from New Zealand reported a recurrence rate of 18.8% (60/320) with a median follow-up of 101 months and no increase in mortality related to recurrent episodes. 11 These studies are all small and have varying diagnostic criteria for acute diverticulitis and its recurrence.…”
Section: Epidemiology and Pathogenesismentioning
confidence: 94%